Efek Proteksi dari Terapi Oksigen Hiperbarik terhadap Ekspresi Bcl-2 Miometrium Rattus norvegicus Bunting yang Terinfeksi oleh Tachyzoite Toxoplasma gondii - Arif Rahman Nurdianto; Aryati Aryati; Mohammad Guritno Suryokusumo; Mufasirin Mufasirin (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Hyperbaric Oxygen Therapy (HBOT) can increase oxygen delivery to tissues and stimulate the formation of H2O2 as a secondary messenger for phosphorylation of nuclear factor kappa beta (NF-kB) which plays an important role in the transcription of the anti apoptotic gene. This study aimed to determine the effects of Hyperbaric Oxygen Therapy (HBOT) in enhancing the expressions of Bcl-2 in the myometrium of pregnant rats infected by Toxoplasma gondii. This study was an experimental study with a randomized control group of post-test only and designed by 37 pregnant Rattus norvegicus Sprague Dawley. Randomly, the rats were divided into four groups. Group A is infected pregnant rats that exposed by 10 sessions of HBOT 2.4 ATA in 3x30 minutes. Group B is non-infected pregnant rats and exposed by 10 sessions of HBOT 2.4 ATA in 3x30 minutes. Group C is infected pregnant rats without any exposure. Group D is non-infected pregnant rats without any exposure. Each infected pregnant rat was given a 103 tachyzoite of T.gondii by intraperitoneal injection. Bcl-2 expressions were measured through immunohistochemistry. All data were analyzed using ANOVA test through SPSS 21 program application. There was a significant difference in Bcl-2 expression between Group A and Group C because p<α (p<0.017). HBOT can increase the expression of Bcl-2 from infected and not infected rat myometrium, in the provision of HBOT 2.4 ATA for 3x30 minutes, twice a day for 5 days.